Utilização de ferramentas digitais para promoção das tecnologias da Embrapa Agroenergia e prospecção de parceria (proposta aplicativo Embrapa Agroenergia) - Barbosa, Patrícia Flávio Dias (2021)
This work seeks to emphasize the importance of using digital tools for greater interaction between Embrapa Agroenergy and its audiences, taking into account technological changes and the large access to the internet. The propositions of Jenkins, Verón, Martin-Barbero and Lemos form the basis for reflective efforts in the challenge of promoting Embrapa's technology transfer actions, mainly to accompany the changes in Embrapa Agroenergy's business model. This study, which resulted in the proposal to apply Embrapa Agroenergy relationship software with its audiences, especially when implemented, with a view to contributing to the interaction of the actors in the Agroenergy chain. The proposal of the Embrapa Agroenergy application is to offer an environment for interaction between researchers, producers, companies and investors, to create opportunities to enable partnerships in research projects, to provide a portfolio of technologies (technological showcase), access to programs: webinar, lives, podcasts, courses and innovation events.